PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL DISCOVERY LEARNING PADA MATERI PERBANDINGAN UNTUK SISWA KELAS VII - Susianingsih, Susianingsih; Anggraini, Rini Dian; Suanto, Elfis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The research background is the importance of mathematics learning instruments as mathematics lesson plans which is arranged by the teacher as a professional worker in order to achieve mathematics learning goals. The available of mathematics learning instruments is limited, and does not refer to 2013’s Curriculum yet. This research is aimed to develop the mathematics learning instruments: syllabus, lesson plans, and student worksheets using the discovery learning model on ratio subject for 7th grade students of SMP/MTs that is categorized as valid and the student worksheets is categorized as practical. This research used ADDIE model The research instruments that used in this research were learning instruments validation sheets and student response questionnaires. The learning instruments are validated by three validators and revised according to the validator’s suggestions, and then tested on thirty two students of Class VII4 of SMP Negeri 8 Pekanbaru for large trials . According to the result of validation data analysis of syllabus, lesson plans, and student worksheets, syllabus and lesson plans were categorized as very valid with the average score for syllabus was 3.69 and 3,46, and student worksheets was were categorized as valid with the average score 3.24. According to the result of student response questionnaires toward the student worksheets practicality, it were categorized as practical with a percentage of 82,26%. According to the result of data analysis and the discussion, it can be concluded that the syllabus, lesson plans using the discovery learning model on ratio subject were very valid, and student worksheets were valid, practical and feasible to be used by 7th grade students of SMP/MTs.Key Words: Discovery Learning Model, Mathematics Learning Instruments, Ratio